The Point of View of the Grammarians In Facilitating, Facilitating And Renewing Arabic Grammar/وجهة نظر النحاة في تيسير النحو العربي وتسهيله وتجديده - Mualim Wijaya (Nurul Jadid University, 2017)
The grammar of the Arabic language is complex and plural, and is built in its ramifications and multiplicity on the basis of philosophical logic. The difficulty of Arabic grammar and the complexity of it is almost agreed among those who teach the language, but we must decide that this difficulty does not stand a barrier to education and that it is a fundamental and important part of the curriculum of learning the language and education. The purpose of this research is to learn about the facilitation of grammar and its problems, knowledge of the soft grammar and its elements in the modern era, and its aim to learn about the phenomenon of teaching Arabic.قواعد اللغة العربية متشعبة ومتعددة، ومبنية في تشعبها وتعددها على أسس منطقية الفلسفية. وصعوبة النحو العربي وكثرة تعقيداته أمر يكاد يتفق عليه بين المشتغلين بتعليم اللغة، إلا أنه ينبغي أن نقرر أن هذا الصعوبة لا تقف حاجرا أمام تعليمه وأنه جزء أساس ومهم من منهج تعلم اللغة وتعليمه. يهدف هذا البحث إلى معرفة تيسير النحو ومشاكله ومعرفة الأصول النحوية الميسرة وأعلامه في العصر الحديث كما يهدف إلى معرفة ظاهرة تعليم اللغة العربية.